The Moderating Role of Social Support on the Effect of Academic Stress on Students’ Engagement - Galugu, Nur Saqinah; Hajeni; Marhani; Pajarianto, Hadi; Elihami; Hikmawati (LETIGES, 2025)
This study aims to identify the relationship between academic stress and students' engagement among santri in Islamic Boarding Schools and explore the moderating role of social support in mitigating the negative impact of academic stress on learning engagement. This research was conducted at SMP Muhammadiyah Boarding School Palopo. The population consisted of 207 students from grades VII to IX. A sample of 136 students was selected using the stratified random sampling technique. Data were collected using questionnaires measuring academic stress, social support, and student engagement, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results show that academic stress has a positive but not statistically significant effect on students' engagement. Conversely, social support has a positive and significant effect and is a considerable moderator that reduces the negative impact of academic stress on learning engagement. In other words, santri who receive strong social support tend to remain actively engaged in the learning process despite facing academic pressures. The limitation of this study lies in the small sample size and its focus on a single Islamic Boarding Schools. Therefore, the findings cannot be widely generalized.